Intention to Use Paylater Feature in a Traveling Platform in Emerging Market: Traveloka Case - Aprianingsih, Atik; Sofyan, Mahardhika Dwi Ananta; Debby, Teresia; Fachira, Ira; Toha, Mohamad (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2023)
This study aims to determine the relationship between customer’s attitude, customer’s subjective norm, and the customer has perceived behavior control on the intention to use PayLater as a payment method in Traveloka. This study uses an online and offline survey conducted in Jakarta and Bandung, with 400 respondents. Structural equation modeling was processed using SmartPLS 3.2.9 for this study. The finding shows that customers’ attitudes, subjective norms, and perceived behavior control positively influence the intention to use PayLater in Traveloka. This study can be used for another application or company that wants to develop a similar payment method to encourage higher use of PayLater. This study explores the inner working of customers’ behavior in connection with the financial service of e-payment, in this case, Traveloka PayLater.